2012
DOI: 10.5552/drind.2012.1226
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Lindane by Wood-Decaying Fungi

Abstract: • The object of this paper is to study the ability of four white-rot fungi (Trametes versicolor, Hypoxylon fragiforme, Chondrostereum purpureum, and Pleurotus ostreatus) and one brown-rot fungus (Gloeophyllum trabeum)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Trametes versicolor, Hypoxylon fragiforme, Chondrostereum purpureum, Pleurotus ostreatus, Gloeophyllum trabeum organic lindane derivatives Amount of lindane was lower in solutions over 70% [46] Fusarium poae F. solani organic lindane derivatives Contaminated soil, 0-600 µg mL −1 10th day of incubation degradation by the two fungal strains demonstrated that the biodegradation of lindane by F. solani (59.4%) was slightly higher than that by the F. poae (56.7%)…”
Section: Fungal Degradation Of Lindanementioning
confidence: 93%
“…Trametes versicolor, Hypoxylon fragiforme, Chondrostereum purpureum, Pleurotus ostreatus, Gloeophyllum trabeum organic lindane derivatives Amount of lindane was lower in solutions over 70% [46] Fusarium poae F. solani organic lindane derivatives Contaminated soil, 0-600 µg mL −1 10th day of incubation degradation by the two fungal strains demonstrated that the biodegradation of lindane by F. solani (59.4%) was slightly higher than that by the F. poae (56.7%)…”
Section: Fungal Degradation Of Lindanementioning
confidence: 93%
“…Regarding biological treatment of lindane, some authors proposed the use of specific bacteria, mixed bacterial cultures and different fungi species isolated from diverse geographic polluted locations to attain it (Gupta et al, 2000;Okeke et al, 2002;Salam and Das, 2012;Ulčnik et al, 2012;Saez et al, 2017). However, lindane has been shown as a toxic molecule in many reported works.…”
Section: Introductionmentioning
confidence: 99%